2022
DOI: 10.35848/1347-4065/ac76fa
|View full text |Cite
|
Sign up to set email alerts
|

Complexity visualization, dataset acquisition, and machine-learning perspectives for low-temperature plasma: a review

Abstract: Low-temperature plasma plays various roles in industrial material processing as well as provides a number of scientific targets. Such rich features in variety are based on its complexities, arising from its diverse parameters. When we consider causalities in these complexities, direct application of machine-learning methods is not always possible. To overcome this difficulty, progresses in plasma diagnostics and data acquisition systems are inevitable, and handling of a large number of data elements is being o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The definition of "plasma dose" will be aided by standardization, which is both a crucial problem and a necessity in the field of plasma medicine. The issue of determining the "plasma dose" using Al is growing in significance despite the fact that there is numerous research for plasma dose assessment in the literature [82,83]. In this study, it is expected that the widespread use of Al in the medical and biomedical fields today will enable the targeted standardization for plasma medicine.…”
Section: Discussionmentioning
confidence: 98%
“…The definition of "plasma dose" will be aided by standardization, which is both a crucial problem and a necessity in the field of plasma medicine. The issue of determining the "plasma dose" using Al is growing in significance despite the fact that there is numerous research for plasma dose assessment in the literature [82,83]. In this study, it is expected that the widespread use of Al in the medical and biomedical fields today will enable the targeted standardization for plasma medicine.…”
Section: Discussionmentioning
confidence: 98%
“…The definition of 'plasma dose' will be aided by standardization, which is both a crucial problem and a necessity in the field of plasma medicine. The issue of defining the 'plasma dose' using Al is growing in significance despite the fact that there is numerous research for plasma dose assessment in the literature [85,86]. In this study, it is expected that the widespread use of AI in the medical and biomedical fields today will enable the targeted standardization of plasma medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the work was extended with betweenness and centrality indices to highlight not only the influentiality of each species on/to the others but also global structures in chemical networks. 83 In this respect, these works have opened up possibilities for simpler prediction of chemical reactions that one would like to understand and/or control. A similar approach for graph construction has been adopted by Sun et al, 84 with a different choice of undirected edges weighted based on steady-state reaction rates.…”
Section: Derivation Of Reduced Reaction Mechanismsmentioning
confidence: 99%
“…In their work, they have constructed a network structure for methane and silane plasmas by representing the species as nodes and reactions as directed unweighted edges and they demonstrated that this network analysis allows one to estimate substantial effects of given species on other ones existing in the network. Then, the work was extended with betweenness and centrality indices to highlight not only the influentiality of each species on/to the others but also global structures in chemical networks 83 . In this respect, these works have opened up possibilities for simpler prediction of chemical reactions that one would like to understand and/or control.…”
Section: Reviewmentioning
confidence: 99%